Estudio comparativo sobre práctica de lactancia materna en el caserío la unión y distrito de la banda de shilcayo, provincia y departamento de San Martín 1996 - Vela Paredes, Anita Ayde (2001)
The present research study applied es·prospectivo, of the descriptive type of comparative and transverse cutting, was performed in the hamlet La Union (rural area} and -estimates the Banda de Shilcayo district (urban area}, through direct observation, surveys and interviews conducted in order to determine if the place of residence influences the practice of breastfeeding.)) It - sample was conformed by 50 mothers in the rural area and the urban area 100. After the corresponding statistical analysis, found that the women of rural practice with greater frequency and time breastfeeding; but they do not employ a proper breastfeeding technique; While in urban areas women apply the best technique, but practice it with less frequency and time. The women of the area rural have many ideas and beliefs wrong on the breastfeeding maternal such as: • not breastfeeding when the mother is menstruating • · Not breastfeed when exposed d...